Pocket Oxford dictionary and thesaurus - Frank R. Abate
A unique new reference that combined the best features of both dictionary and thesaurus, The Oxford Dictionary and Thesaurus was the first American reference work to offer integrated dictionary and thesaurus entries. Now this revolutionary volume is available in a convenient paperback format that is perfect for the casual user